EVALUASI SISTEM PERLINDUNGAN PADA BTS (BASE TRANSCEIVER STATION) ARENA REMAJA PONTIANAK PT.INDOSAT TERHADAP SAMBARAN PETIR - ., Joninton (Jurnal Teknik Elektro Universitas Tanjungpura, 2016)
Abstract This  study  discusses  about  external  and  internal protection at BTS Arena Remaja Pontianak PT.Indosat. External protection was analyzed withRolling Sphere Method and BTS’s height is 40 meters. The efficiency of BTS Arena Remaja is 0,93 with  protection  level  II  and  the  radius  of  rolling sphere is 30 meters so it could be said that the protection chamber such as shelter and generator room are safe from direct lightning. Furthermore, the grounding  resistance  number  from  that measurements is around 0,02-0,07 ohm. At internal protection known that overvoltage will be occurs with peak currents in Kalimantan Barat, determined base on the average of   peak currents in the earth, as non ideal value is 36,16 kA which can damage the equipment in protection chamber through the electric power line and signal line (coaxial cable). More voltage in the electrical transmission is 7753,78 kV and in the signal (coaxial cable)  minimum  0.07764  kV and maximum0.07909 kV with the fault of current is 36.16 kA. That voltage will  continue  flowing  to  the  equipment,  so  there should be some equipment protection. For an alternative, mounting arresters can be done in stages according to the characteristics. Keyword     :     Eksternal     Protection,     Internal Protection, Rolling Sphere Method